Questões ortográficas: Rafael Bluteau e o Novo Acordo num percurso historiográfico - Silva, Raisimar Arruda da (2010)
This dissertation is subject an examination of the orthography developed by Rafael Bluteau. It follows the line of research of history and description of the Portuguese language. The season is marked in the pseudoetimológico precisely in the second half of the seventeenth century and the first of the eighteenth century. Since the purpose of regulating the spelling Portuguese Bluteau edit spelling rules and laws, based on the origin of words. The topic will be corpus the Vobabulario Portuguez and Latino. The questioning of this research is the discovery of spelling rules, which have not yet been achieved, today. In other words, to what extent the problems pointed out by Bluteau repeat, in the nineteenth century. It is in this plot of inaccuracies that need arises to search for such problems. The objective that guides this research is to contribute to studies of the spelling of the English language. Therefore, described the rules of spelling Rafael Bluteau, and then make the comparison with the New Deal Checker. To give methodological foundation for this research, we followed the tenets of historiography Linguistics, based on work by Konrad Koerner through its three principles: context (retracted Bluteau the historical and cultural context of his time), immanence (described in and then explain its proposal spelling, using your terminology) and use (closer to the proposed Rafael Bluteau with the New Accord, using modern terminology). The results were satisfactory. After examining the spelling of Rafael Bluteau to compare it with the New Accord, there was some rejection of his spelling rules by the Portuguese society of the eighteenth century, due to the naturalness of the author, although there was political will on the part of D. John V